Test Data Generation for Database Applications - Agrawal, Pooja; Chandra, Bikash; Emani, Venkatesh; Garg, Neha; Sudarshan, S. (ICDE (Demo), 2018)
Unit test cases have become an essential tool to test application code. Several applications make use of SQL queries in order to retrieve or update information from a database. Database queries for these applications are written natively in SQL using JDBC or using ORM frameworks like Hibernate. Unit testing these applications is typically done by loading a fixed dataset and running unit tests. However with fixed datasets, errors in queries may be missed. In this demonstration, we present a system that takes as input a database application program, and generates datasets and unit tests using the datasets to test the correctness of function with queries in the application. Our techniques are based on static program analysis and mutation testing. We consider database applications written in Java using JDBC or Hibernate APIs. The front-end of our system is a plugin to the IntelliJ IDEA IDE. We believe that such a system would be of great value to application developers and testers.